SOCIAL PHILOSOPHICAL FACTORS OF IMPROVING THE ELECTORAL SYSTEM - Xo’jaxonov Islomxo’ja Abdullokhan o’g’li (International Engineering Journal For Research & Development, 2021)
The electoral system is a set of electoral procedures and legal norms that establish them. The electoral system includes the existing order on the formation of state representative bodies and on the involvement of citizens in elections, the organization of elections and the deputy's relations with voters, all electoral rights of citizens (see suffrage).`